Pass-through in Colombia’s Unregulated Retail Electricity Market - Perez, Alex; Carabali, Jaime; Meneses, Luis (International Journal of Energy Economics and Policy, 2022)
This study analyzes the pass-through of wholesale costs to retail prices for unregulated users in the Colombian electricity market, using monthly data from 2012 to 2019. This period encompasses moments with and without an El Niño phenomenon. We use an empirical model to analyze the pass-through heterogeneity according to the characteristics of users and firms, showing that the pass-through is incomplete, differs according to the presence of El Niño, and is heterogeneous. The pass-through was greater from September 2015 to May 2016 because an El Niño caused hydrological resource scarcity and several critical thermal plants halted operations. In other words, the pass-through tends to be more comprehensive during an El Niño event. Additionally, the pass-through differs between firms with a high concentration of the market and the remaining firms and between urban and non-urban users.